Cutaneous melanoma in children and adolescents: The EXPeRT/PARTNER diagnostic and therapeutic recommendations. (26th June 2021) - Ferrari, Andrea; Lopez Almaraz, Ricardo; Reguerre, Yves; Cesen, Maja; Bergamaschi, Luca; Indini, Alice; Schneider, Dominik T.; Godzinski, Jan; Bien, Ewa; Stachowicz‐Stencel, Teresa; Eigentler, Thomas K.; Chiaravalli, Stefano; et al.
Abstract: Cutaneous melanoma is rare in children and, like other very rare pediatric tumors, it suffers from a shortage of knowledge and clinical expertise. The clinical management of pediatric melanoma is often challenging. Its clinical and pathological diagnosis may be difficult, and there is no standard treatment. In the absence of specific treatment guidelines, young patients are generally treated following the same principle as for adults, but concern remains about their access to clinical trials and new drugs, which have been shown to dramatically change the natural history of advanced melanoma. This paper presents the internationally recognized recommendations for the diagnosis and treatment of children and adolescents with cutaneous melanoma, established by the European Cooperative Study Group for Pediatric Rare Tumors (EXPeRT) within the EU‐funded project called PARTNER (Paediatric Rare Tumours Network ‐ European Registry). Main recommendations for melanoma are to discuss pediatric patients in multidisciplinary teams that include both pediatric oncologists and specialists in adult melanoma; to enroll patients in prospective trials, if available; to collect data in national–international databases; and to develop an effective international collaboration between pediatric and adult melanoma groups in order to facilitate the transfer of potentially effective new agents from the adult to the pediatric setting.